Genetic Factors Associated with Slow Progression of HIV among Perinatally-Infected Indian Children - Chaudhuri, Riya Pal (Indian Pediatr, 2014)
OBJECTIVES: To study the association between common AIDS restriction genes and slow disease progression among perinatally-infected children in India. METHODS: ART-naïve children were identified and selected host factors including CCR5-Δ32, SDF1-3’A, CCR5-59029G, HLA-B*27, B*57 were studied using allele-specific PCR-RFLP and SSPGo HLA typing kits. RESULTS: Among 165 children, 10 (6%) long-term non-progressors and 8 (5%) slow progressors were identified. For comparison, 12 children with normal progression of HIV were included. The frequencies of CCR5-Δ32 deletion, SDF1-3’A and CCR5-59029G did not differ significantly. HLA-B*27 and B*57 were observed only in long-term non-progressors or slow progressors, who also harbored either SDF1-3’A and/or CCR5-59029G. CONCLUSIONS: There is an association between host genetic factors and slow disease progression in this population.